Induction immunosuppression for combined heart–lung transplantation. Issue 10 (7th September 2016) - Hayes, Don; McConnell, Patrick I.; Yates, Andrew R.; Tobias, Joseph D.; Galantowicz, Mark; Mansour, Heidi M.; Tumin, Dmitry
Abstract: Background: Research on induction immunosuppression in patients undergoing combined heart–lung transplantation (HLTx) is limited. Methods: The United Network for Organ Sharing database was queried from 2000 to 2013 to examine the influence of induction immunosuppression for combined HLTx in adult (≥18 years) and adolescent (≥12 and <18 years) recipients. Results: Of 394 eligible combined HLTx cases (361 adults, 33 adolescents), 384 were included in univariate Cox analysis and 116 in the multivariate Cox model. Univariate analysis demonstrated no differences in survival by induction medication and no difference among the most common maintenance immunosuppression regimens. Adjusting for use of corticosteroids, multivariate analysis demonstrated no benefit of basiliximab (HR=3.582; 95% CI: 0.966, 13.279; P =.056), thymoglobulin/antilymphocyte globulin (ALG)/antithymocyte globulin (ATG) (HR=0.808; 95% CI: 0.134, 4.888; P =.817), alemtuzumab (HR=0.369; 95% CI: 0.087, 1.563; P =.176), or other induction medications (HR=1.511; 95% CI: 0.146, 15.610; P =.729), compared to no induction medication, with respect to mortality hazard post‐HLTx. There were also no differences in treated acute rejection episodes by type of induction immunosuppression. Conclusions: Induction immunosuppression with contemporary agents does not improve survival after combined HLTx.